E-Government in Gowa District (Study on Diskominfo at Gowa District) - Sri Dewi Mulyana Nur Tadrin; Sulmiah Sulmiah (Universitas Negeri Makassar, 2022)
This study aims to determine e-Government in Gowa Regency as well as supporting and inhibiting factors in the implementation of e-Government in Gowa Regency. This study uses a qualitative approach. The data collection used was interview, documentation, and observation. The data obtained from the research results were processed using an interactive analysis model, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that e-Government in Gowa Regency (Study at Diskominfo Gowa Regency) is based on four indicators that must be achieved in the implementation of e-Government, namely: efficiency is good, effectiveness is not good, transparency is good and accountability is not good. The effectiveness indicator is said to be not good because there are constraints in terms of the budget which causes the planning to not be achieved in accordance with the objectives. Meanwhile, on the data accountability indicators, the accuracy of which can be guaranteed by Diskominfo is only on the Gowa Public Relations website, not on the correctness of the reporting by each SKPD that is entered into the website provided.